Leadership gender disparity in the fifty highest ranking North American universities: Thematic analysis under a theoretical lens. Issue 1163 (9th August 2021) - Azizi, Hawmid; Abdellatif, Waleed; Nasrullah, Muazzam; Ali, Shozab; Ding, Jeffrey; Khosa, Faisal
Abstract : Background: Despite changes in the discourse around gender distributions within academic leadership, women continue to be under-represented in academia. Our study aims to identify the extent of gender disparity in the academic leadership in the top 50 North American universities and to critically analyse the contributing factors through a comprehensive theoretical framework. Methods: We adopted the theoretical framework of leadership continuum model. A retrospective analysis of the gender of the leadership ranks was conducted between December 2018 and March 2019 for the top 50 universities in North America (2019 Quacquarelli Symonds World University Ranking system). The leadership hierarchy was classified into six tiers. Results: A total of 5806 faculty members from 45 US and five Canadian universities were included. Women were overall less likely to be in a senior leadership role than men (48.7% vs 51.3%; p value=0.05). Women accounted for fewer positions than men for resident/chancellor (23.8% vs 76.2%; p value<0.001), vice-president/vice-chancellor (36.3% vs 63.7%; p value<0.001), vice provost (42.7% vs 57.3%; p value=0.06), dean (38.5% vs 61.5%; p value<0.001) and associate dean (48.2% vs 51.8%; p-value=0.05). Women however were in a greater proportion in the assistant dean positions (63.8% vs 36.2%; p value<0.001). Conclusion: Leadership gender imbalance is trans-organisational and transnational within the top 50 universities of North America and progressively widens towards the top leadership pyramid. This correlates with the lack of women leadership progress and sustainability in later cycles of the leadership continuum model (beyond assistant dean).